Ibn Tofail’s University students’ satisfaction evaluation towards distance learning and its impacts on the students’ mental health during the Covid 19 Confinement. (Bangladesh Journal of Medical Science, 2020)
Aims, objectives and methods: The study we have conducted aims to evaluate Moroccan students’ satisfaction level with regard to the use of distance learning platforms during the Covid 19 confinement period. We also attempt to examine the impact of distance learning on the students’ mental health.Our research has demonstrated that imposing distance learning as a learning process to students produces a substantial stress level within 49% of the investigated student population.Indeed, the students’ full immersion in distance learning process has obviously arose technical and pedagogical brakes within (87%) of the questioned student population, and also psychological brakes within (27%) of the respondent population. Furthermore, the particularity of this confinement’s period has brought to light three students’ categories regarding the use of distance learning in their training and learning process and behavior.Recommendations:Our study’s results can be considered very relevant because they show a clear correlation between the adoption of distance learning, as a new teaching approach, and, the perceived stress level (49%) involved during this process. Therefore, the clear necessity of material, pedagogical and psychological supports to be implemented during this transition stage.Bangladesh Journal of Medical Science Vol.19(0) 2020 p. S 51-S 57